Alasan Untuk Tetap Tinggal Di Kawasan Yang Tergenang Rob Dan Terjadi Penurunan Tanah, Di Genuk Semarang - Parfi Khadiyanto (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
Humans as economic beings are always trying to find opportunities to earn income, that is by working anything and anywhere. As a result humans will find a place of life that is considered suitable for him in doing business to get a living space to build a settlement. There are two main options: choosing a comfortable place, and the second chooses a place close to the source of income, the resoltante of the two choices will produce a suitable land choice for himself. The question is, from the two options turned out that the location close to the source of income is more prominent than the need for comfort. There is a settlement whose location is unfit for habitation, but the community is willing to embrace the place just because the location is close to the source of income, which is around the industrial area in Semarang. This location is always inundated by tidal flood, dense, polluted by the industry, land degradation occurs, but the number of inhabitants comes 3 times more than the amount that comes out.The purpose of this study is to find out the reasons for the community to stay afloat, live in the area of the settlements that are integrated, experiencing a of rob inundation and the decline of land in the District of Genuk Semarang. The research method is done descriptively quantitative, with correlation analysis.The findings show that, the strength to survive is the economic factor kaeran, that is close to the industrial area, easy access, and facilities for children's education is also easy.